A Review of Scales to Evaluate Sleep Disturbances in Movement Disorders - Kurtis, Mónica M.; Balestrino, Roberta; Rodriguez-Blazquez, Carmen; Forjaz, Maria João; Martinez-Martin, Pablo (Frontiers in Neurology, 2018)
Patients with movement disorders have a high prevalence of sleep disturbances that can be classified as 1) nocturnal sleep symptoms, such as insomnia, nocturia, restless legs syndrome (RLS), periodic limb movements (PLM), obstructive sleep apnea (OSA), and REM sleep behaviour disorder; and 2) diurnal problems that include excessive daytime sleepiness (EDS) and sleep attacks. The objective of this review is to provide a practical overview of the most relevant scales that assess these disturbances in order to guide the choice of the most useful instrument/s depending on the line of research or clinical focus. For each scale, the reader will find a brief description of practicalities and psychometric properties, use in movement disorder cohorts and analysed strengths and limitations. To assess insomnia, the Pittsburgh Sleep Quality Index, a generic scale, and three disease-specific scales: the Parkinson Disease Sleep Scale (PDSS), the PDSS-2, and Scales for outcomes in PD-Sleep-Nocturnal Sleep subscale are discussed. To evaluate nocturia there are no specific tools, but some extensively validated generic urinary symptom scales (the Overall Bladder Questionnaire and the Overactive Bladder Symptom Score) and some PD specific scales that include a nocturia item are available. To measure RLS severity, there are currently four domain specific generic scales: The International Restless Legs Scale, the Johns Hopkins Restless Legs Severity Scale, the RLS-6 measure, a Paediatric RLS Severity Scale, the Augmentation Severity Rating Scale (a scale to evaluate augmentation under treatment) and several instruments that assess impact on quality of sleep and health related quality of life. To evaluate the presence of PLM, no clinical scales have been developed to date. As far as OSA, commonly used instruments such as the Sleep Apnea Scale of the Sleep Disorders Questionnaire, the STOP-Bang questionnaire and the Berlin Questionnaire are reviewed. Three scales have been extensively used to assess EDS: the generic Epworth Sleepiness Scale, the Stanford Sleepiness Scale, and the PD specific Scales for outcomes in PD-Sleep-Daytime sleepiness subscale. To date, only the Inappropriate Sleep Composite Score (ISCS) specifically evaluates propensity to sleep attacks.